2019
DOI: 10.1080/15548627.2019.1628544
|View full text |Cite
|
Sign up to set email alerts
|

IRGM restrains NLRP3 inflammasome activation by mediating its SQSTM1/p62-dependent selective autophagy

Abstract: IRGM is an established genetic risk factor for Crohn disease (CD) and several other inflammatory disorders. However, the mechanisms employed by IRGM to restrain the inflammation are not known. In our recent study, we showed that IRGM negatively regulates NLRP3 inflammasome activation. IRGM employs 2 parallel approaches to constrain inflammasome activation. First, IRGM directly interacts with NLRP3 and PYCARD/ASC, and mediates their SQSTM1/p62-dependent macroautophagic/autophagic degradation. Second, IRGM imped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 1 publication
0
34
0
Order By: Relevance
“…Because it has been demonstrated that autophagy has important effects on the induction of the inflammatory reaction, 6 , 24 we investigated the relationship between Sal-miR-58-induced autophagy and inflammation in Ang II-treated VSMCs. Western blot analysis showed that treating VSMCs with Ang II clearly reduced the expression of Beclin1 and Atg5, which was reversed by Sal-miR-58 transfection, as evidenced by increased expression of Beclin1 and Atg5 as well as by enhanced conversion of LC3BI to LC3BII ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Because it has been demonstrated that autophagy has important effects on the induction of the inflammatory reaction, 6 , 24 we investigated the relationship between Sal-miR-58-induced autophagy and inflammation in Ang II-treated VSMCs. Western blot analysis showed that treating VSMCs with Ang II clearly reduced the expression of Beclin1 and Atg5, which was reversed by Sal-miR-58 transfection, as evidenced by increased expression of Beclin1 and Atg5 as well as by enhanced conversion of LC3BI to LC3BII ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that IRGM is a key negative regulator of NLRP3 inflammasome activation by interacting with NLRP3 and ASC and subsequently inhibiting inflammasome assembly [71]. In line with this, IRGM mediates the autophagic degradation of NLRP3 components [72]. However, there is still relatively less known regarding the function of IRGM in cancer.…”
Section: Autophagy-related Moleculesmentioning
confidence: 95%
“…Previous studies have shown that autophagy regulates the activation of microglia and in ammatory response [69][70][71]. The activation of NLRP3 in ammasome is inhibited by autophagy through the clearance of damaged mitochondria degradation of the NLRP3 in ammasome [42,72,73]. Therefore, we used western blot analysis to detect the expression of NLRP3 and related in ammatory factors, IL-18 and IL-1Ī².…”
Section: Autophagy Induction Attenuated the Ntg-evoked Activation Of mentioning
confidence: 99%